Comment les étudiants en formation à l'enseignement pensent-ils l'aide aux élèves en difficulté ? - Sandrine Breithaupt (Nantes Université, 2012)
This paper presents the results of a research that was conducted in the frame of initial training (during the last year of a three years training program) for primary teachers in the region of Vaud (Switzerland). It aimed at understanding how student teachers perceive pupils with special learning needs and, more specifically, what they mention when they refer to the learning difficulties faced by pupils and, finally, what type of solution they consider putting in place in order to help pupils overcome the difficulties they encounter when they learn. The article explores these questions through the analysis of documents written by the students after a seminar of analysis of teaching practices. The results show that students focus their attention on three different categories of difficulties: the « acquisition of conceptual knowledge », « observable attitudes and behaviour » and « motivational and cognitive aspects ». Mostly, they evoke two types of intervention to resolve these problems: using a psychologist and placing the pupils in small groups of support.